Designing two-dimensional WS2 layered cathode for high-performance aluminum-ion batteries: From micro-assemblies to insertion mechanism. (June 2020) - Zhao, Zhongchen; Hu, Zhengqiang; Li, Qiang; Li, Hongsen; Zhang, Xiao; Zhuang, Yidan; Wang, Feng; Yu, Guihua
Graphical abstract: The novel star-shaped 2D WS2 microsheet assemblies are explored as promising cathode material for aluminum-ion batteries. Their aluminum reactivity mechanism involving reaction AlCl4 − and S 2− anions has been understood via DFT calculations, ex-situ XPS and XRD. Highlights: Novel approach for designing of the star-shaped 2D WS2 microsheet assembly. Deep insights into the intercalation mechanism of chloroaluminate anions in 2D cathode. Remarkable cycling stability with high reversible capacities of the 2D WS2 microsheets-assembled cathode for AIBs. Abstract: Owing to the high abundance, inherent safety, and three-electron redox properties of aluminum, aluminum-ion batteries (AIBs) are promising candidates for the next-generation battery technologies with high energy-to-price ratio. Despite recent great progress in finding appropriate electrolyte, an on-going research focus of the AIBs remains to be exploiting host electrodes for the large aluminum (complex) ions. Herein, a star-shaped two-dimensional (2D) WS2 microsheet assembly cathode substitute is prepared and applied in AIBs for the first time. The in-depth study with density functional theory (DFT) calculations, ex-situ X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) reveals an explicit intercalation mechanism of chloroaluminate anions (AlCl4 − ) in the WS2 electrode. Benefiting from their structural configuration, the star-shaped 2D WS2 microsheet assemblies display a highly reversible capacity of 254 mA h g −1 at a current density of 0.1 A g −1, a superior rate capability (86 mA h g −1 at 5 A g −1 ), and a favorable cycling stability (119 mA h g −1 remained after 500 cycles at 1 A g −1 ). The synthetic approach and the proposed mechanism could pave the way for the further development of high-performance AIBs.